Instrumentos para implementação do processo de enfermagem em uma Unidade de Terapia Intensiva Pediátrica - Silva, Amanda Benício da (2013)
INTRODUCTION: Caring about children in critical stage at Pediatric Intensive Care Unit (PICU) elevates Pediatric Nursing to a level totally different and more exigent, as it requires that nurses are experts in this specialty. The Systematization of Nursing Care is a tool which can contribute in a significant way to the quality of care provided these patients. The elaboration of instruments permits to the nurse modifies and organizes new models to facilitate the application of nursing process, directing and qualifying the assistance. Due to the related situation, it was chosen to do the present study, which is based on the Theory of Basic Human Needs by Horta. The utilization of theoretical references in the professional nursing practice is a facilitator to effective actions of caring that privilege the human being inserted in an environment, in the intuit of reestablishing health by means of nursing care. OBJECTIVES: To build a tool for the implementation of nursing process at a Pediatric Intensive Care Unit. METHOD: It is a methodological research that was developed at the Pediatric Intensive Care Unit of Lauro Wanderley University Hospital (LWUH), which is situated at campus I of the Federal University of Paraíba, in João Pessoa - PB. The population and the sample are formed by clinical nurses of the mentioned unit and by professors of the Federal University of Paraíba. The project was approved by the Research Ethics Committee of Lauro Wanderley University Hospital, under protocol CAAE: 06863212.8.0000.5183. The research was divided in three stages: Stage 1 - Identification of empiric indicators of the Basic Human Needs in children hospitalized in Intensive Care Unit. Stage 2 - Development of diagnostic enunciations and nursing interventions. Stage 3 - Structuring of tool for the implementation of nursing process. RESULTS: It was done an exhaustive literature review to identify the needs of children hospitalized in Intensive Care Unit, basing on the proposals of Horta, resulting in obtainment of 268 empiric indicators for this clientele, of which 173 were validated by clinical nurses and professors. After, based on these validated indicators, they were developed 45 diagnostic enunciations and 90 nursing interventions, that were subsequently used in the structuring of tool for the implementation of nursing process in a Pediatric Intensive Care Unit (PICU). This instrument was divided into two parts: the historical of Nursing, named as the first phase of Nursing Process, according to Resolution 358/2009; the second part corresponds to the planning of nursing care, including the other phases of nursing process, making possible to the nurse establish diagnostics and nursing interventions, and do the evaluation. CONCLUSION: It is expected that this instrument can be used and validated by nurses and that it favors the implementation of nursing process in the Pediatric Intensive Care Unit, to promote quality nursing care.